(3GdfbhO hGdeUGQa hGdfXQjI GdfbOjIs - (3fGXe eMeO fhQj(B, (3GdTeQjs ((3YeGf(B:s (3OGQ RgQGf ddfTQ(B,s, 2006)
(3aj GdfbhO;fTCI GdfbhO hhXGFagG;GdfXe hGdbhGYO GdfbOjI,bjeI GdfbhO hJZjQgG,aj GdeUGQa,GdGFJeGf aj GdGfXeI GdGbJUGOjI GdeNJdaI,CfhGY GdGFJeGf GdeUQaj hhXGFag,GdLgGR GdeUQaj,GdfTGW GdGFJeGfj ddeUGQa GdJLGQjI,GdeUGQa GdeQcRjI hGdeDSSGJ GdeGdjI GdhSjWI,eaghe hGfhGY YQV GdfbO heMOOGJg,aj GdSjGSI hGdfXQjGJ GdfbOjI,GdfXQjI GdfbOjI GdcdGSjcjI,GdfXQjI GdfbOjI GdcjfRjI,Cge GdGVGaGJ Ydi GdfXQjGJ GdfbOjI GdSGHbI,GdWdH Ydi GdfbhO,Gge GdeTcdGJ GdGbJUGOjI hGdfbOjI GdeYGUQI,GdSjGSI GdfbOjI hGdfTGW GdGbJUGOj,GdSjGSI GdeGdjI hGdSjGSI GdfbOjIs
(3HHdjhZQGajG(B:(3U(B.475-481s
Keywords: (3GdSjGSI GdeGdjIs; (3GdfbhOs